CLINICAL CRITERIA FOR THE OUTCOME FORECAST OF ACUTE EXOGENOUS INTOXICATIONS WITH ORGANOPHOSPHORUS PESTICIDES - Petko Marinov; Snezha Zlateva; Dobri Ivanov; Georgi Bonchev; Yulichka Sabeva; Kaloyan Georgiev; Ivaylo Vazharov (Peytchinski Publishing, 2017)
Purpose: The wide-spread use of organophosphorus pesticides (OPP) and their substantial toxicity determine the high frequency of poisoning with them. Despite the modern treatment methods, the acute exogenous intoxications (AEI) continue to exhibit high lethality and are the source of one of the most serious problems in the clinical toxicology. A number of not commonly accepted criteria have been suggested to estimate the gravity of the organophosphorous intoxication. Until now no system of clinical criteria exists that would forecast the outcome of this type of acute poisoning. The aim of this study is to develop an outcome forecast of AEI with OPP with the help of basic clinical criteria. Materials/Methods: The subjects of the study are 160 patients. We explore the significance of five of the most typical clinical indicators of the acute poisoning with OPP for the outcome of the intoxication and the need of artificial pulmonary ventilation, with the aid of discriminatory statistical analysis. The selected indicators form a discriminatory model with automatically built discrimination function. Results: The obtained classification coefficients allow us to construct a forecast matrix containing score estimates designed for practical applications.